Follistatin during pregnancy and its potential role as an ovarian suppressing agent - Köninger, Angela; Strowitzki, Thomas (European journal of obstetrics & gynecology and reproductive biology, 2017)
Objective Ovarian quiescence is a common condition during pregnancy. In vitro, follistatin, an antagonist of follicle-stimulating hormone, blocks follicular development at early stages, and its serum levels increase during pregnancy. A possible surrogate biomarker of ovarian arrest during pregnancy is a decrease in anti-mullerian hormone (AMH) levels followed by an increase in these levels on the second day after labor. The purpose of this study was to determine whether follistatin could act as an ovarian-suppressing agent during pregnancy. Follistatin levels and AMH levels were determined at various stages of pregnancy and postpartum. Study design The follistatin and AMH levels of 69 patients were retrospectively determined with the AMH Gen II ELISA and with the Human Follistatin Quantikine ELISA Kit. For 49 patients, samples were available from various trimesters for cross-sectional analysis; for the other 20, samples were available longitudinally from day one before labor and then daily on days 1 through 4 after labor. Statistical significance was determined with linear regression, the Friedman rank sum test and the Wilcoxon-Nemenyi-McDonald-Thompson post hoc test. Results The behavior of follistatin levels was exactly opposite that of AMH levels: Follistatin levels increased significantly during pregnancy and on the first day after parturition but declined afterwards, whereas AMH levels decreased significantly during pregnancy and increased after labor. Conclusion Follistatin can induce ovarian arrest during pregnancy.
Gesehen am 02.11.2018